THE DEVELOPMENT OF LEARNING MANAGEMENT PROCESS TO ENHANCE CREATIVE THINKING THROUGH PROJECT BASED LEARNING AND INTEGRATION OF SUFFICIENCY ECONOMY PHILOSOPHY. - Ruankum, Nutakarn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
Abstract This research aimed to 1) develop the learning management process to enhance creative thinking through project-based learning and integration of sufficiency economy philosophy, 2) investigate the effectiveness of implementation of the learning management process to enhance creative thinking through project-based learning and integration of sufficiency economy philosophy, 3) explore the satisfaction of pre-service students toward the learning management process to enhance creative thinking through project-based learning and integration of sufficiency economy philosophy.The participants of this study were sixty pre-service elementary teachers, College of Teacher Education, Phranakhon Rajabhat University who enrolled in the Integration of Learning Management of Elementary Level Course in the second semester of the academic year 2017. They were selected by simple random sampling. The research instruments consisted of the creative thinking test, task evaluation form, and student’s satisfaction form. The data were analyzed using descriptive statistics, percentage, mean and standard deviation. The results indicated that the learning management process to enhance creative thinking through project-based learning and integration of sufficiency economy philosophy consisted of three elements: (1) Integration of sufficiency economy philosophy is composed of Person, Integrated Management, Sufficiency economy philosophy, Learning resources, and Evaluation (2) Project-based Learning approach has six steps are Introduction, Planning, Doing, Analysis, Presentation and Evaluation (3) Creative thinking is consist of Think creativity, Work creativity with others, and Implement Innovations; (= 4.73) The pre-service teacher’s creative thinking between experimental and control groups was different at .01 level of significance; The pre-service teacher’s satisfaction towards the use of the learning management process was found that at the highest level ( = 4.53 ).